Resonant RF electromagnetic field input in the helicon plasma ion source - Alexenko, O.V.; Miroshnichenko, V.I.; Mordik, S.N. (Вопросы атомной науки и техники, 2014)
Spatial distribution of RF electromagnetic field absorption by a plasma electron subsystem of ion source is studied. An ion source operates in a helicon mode (wci < w < wce < wpe). A simplified model of plasma RF source is used for investigations. Calculations were performed for two particular geometrical dimensions of a discharge chamber with the assumption of two symmetrical modes excitation at two different pressure values of plasma forming gas (helium, hydrogen). The ion source injector parameters of IAP NASU nuclear scanning microprobe were taken for calculations. The calculations show a resonant behaviour of integral RF power absorption as a function of the external magnetic field at a fixed plasma density. Sharpness of resonances becomes smaller as plasma forming gas pressure grows. There is a distribution topography of absorbed power in a discharge chamber for the cases under research. The possible extracted ion current density is evaluated under Bohm criterion. Исследуется пространственное распределение поглощения ВЧ-электромагнитного поля электронной подсистемой плазмы источника. Источник ионов работает в геликонном режиме ( wci < w < wce < wpe). Для исследований используется упрощенная модель плазменного ВЧ источника. Расчеты проводились для двух конкретных геометрических размеров разрядной камеры в предположении возбуждения симметричных мод при двух различных значениях давления рабочего газа гелия, водорода. Для расчетов выбраны параметры источника ионов инжектора ядерного сканирующего микрозонда ИПФ НАН Украины. Результаты численного счета показывают резонансный характер интегрального поглощения ВЧ мощности в зависимости от значения величины магнитного поля при фиксированной плотности плазмы. Острота резонансов уменьшается с ростом давления рабочего газа. Приводится топография распределения величины поглощаемой мощности внутри объема разрядной камеры для рассмотренных случаев. На основании критерия Бома делается оценка значения плотности возможного извлекаемого ионного тока. Дослiджується просторовий розподiл поглинання ВЧ-електромагнiтного поля електронною пiдсистемою джерела. Джерело iонiв працює в гелiконному режимi( wci < w < wce < wpe) . Для дослiджень використано спрощену модель плазмового ВЧджерела. Розрахунки проводились для двох конкретних геометричних розмiрiв розрядної камери в припущеннi збудження симетричних мод при двох рiзних значеннях тиску робочого газу гелiя, водню. Для розрахункiв обрано параметри джерела iонiв iнжектора ядерного скануючого мiкрозонду IПФ НАН України. Результати чисельного розрахунку показують резонансний характер iнтегрального поглинання ВЧ потужностi в залежностi вiд значення величини магнiтного поля при фiксованiй густини плазми. Гострота резонансiв зменшується з ростом тиску робочого газу. Наведено топографiю розподiлу величини потужностi, що поглинається всерединi об'єму розрядної камери, для розглянутих випадкiв. На пiдставi критерiю Бома зроблено оцiнку значення густини можливого екстрагуємого iонного струму.